Angel in contemporary art. Iconology as regards to a presence of the absence - Caliandro, Stefania (Laboratório Editorial FCL-UNESP, 2010)
The angel’s iconology, in the light of Walter Benjamin and Jean-François Lyotard’s reflections on this theme, leads us to analyse both the effects of presence and a presentification of the absence that this figure enables in various media of artistic creation.